Efficacy of Tofacitinib in the Treatment of Axial Spondyloarthritis : Efficacy of Tofacitinib - Khan, Abdul Waris; Khan, Midrarullah; Khan, Najeebullah; Shah, Qasim (Pakistan Journal of Health Sciences, 2023)
Tofacitinib is a janus kinase enzyme inhibitor used in the treatment several inflammatory conditions. It orchestrates cytokine communication for numerous natural and adaptive immunological responses and underlie the intricate pathophysiology of AS, are directly bound by JAK inhibitors and their intracellular catalytic activity is controlled. For the medical care of older individuals with axial spondyloarthritis, tofacitinib, an oral JAK inhibitor, is being studied. Objective: To analyze the efficacy of tofacitinib in the treatment of axial spondylarthritis in adult patients. Methods: During the time frame of 1st November 2022 till 31st October 2023 at the department of rheumatology, Lady Reading Hospital, Peshawar, patients with active axial spondyloarthritis who fulfilled the modified New York criteria and who were refractory to NSAIDs were registered in this study. Patients were randomized to receive tofacitinib 5mg x BID for 12 weeks, or a placebo, in equal groups (A and B). The study's major end goal was the evaluation of Spondyloarthritis International Society responses evaluating a 20% improvement (ASAS20) at week 12. Results: 44 patients were enrolled (22 in each group). The mean age of tofacitinib arm was 41.19 ± 5.075 years versus 39.83 ± 4.989 years in placebo group. Tofacitinib was effective in 17 patients (77.3%) as compared to 07 patients (31.8%) in placebo group. Treatment response was significant higher (p = 0.002) with tofacitinib. Conclusions: Tofacitinib considerably out-performed a placebo when used to treat people with active axial spondyloarthritis.